2021
DOI: 10.1002/adma.202007623
|View full text |Cite
|
Sign up to set email alerts
|

Disorder‐Induced Material‐Insensitive Optical Response in Plasmonic Nanostructures: Vibrant Structural Colors from Noble Metals

Abstract: Materials show various responses to incident light, owing to their unique dielectric functions. A well‐known example is the distinct colors displayed by metals, providing probably the simplest method to identify gold, silver, and bronze since ancient times. With the advancement of nanotechnology, optical structures with feature sizes smaller than the optical wavelength have been routinely achieved. In this regime, the optical response is also determined by the geometry of the nanostructures, inspiring flourish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…The effective refractive index of the AgNPs-SCN slab is retrieved using a well-established S-parameter retrieval technique ( 39 , 40 ). The effective parameters are greatly affected by geometrical parameters such as size and dispersion of the NPs; for instance, one can suppress the contribution of material properties to absorption spectra by randomly arranging metallic NPs ( 28 ). Therefore, we realistically model the AgNPs-SCN slab based on measured scanning electron microscope (SEM) images and atomic force microscope (AFM) data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effective refractive index of the AgNPs-SCN slab is retrieved using a well-established S-parameter retrieval technique ( 39 , 40 ). The effective parameters are greatly affected by geometrical parameters such as size and dispersion of the NPs; for instance, one can suppress the contribution of material properties to absorption spectra by randomly arranging metallic NPs ( 28 ). Therefore, we realistically model the AgNPs-SCN slab based on measured scanning electron microscope (SEM) images and atomic force microscope (AFM) data ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A leap in thermoelectric performance from the current status requires innovative strategies that can simultaneously optimize both electronic and phonon transports. Recently Roychowdhury et al demonstrated such an approach based on the optimization of order–disorder occupancy of the constituent atoms in a lattice, which tremendously improved the thermoelectric performance of polycrystalline AgSbTe 2 . , The core of the atomic order–disorder optimization strategy stems from the manipulation of disorder-induced localized electronic states. The presence of inherent atomic disorder is ubiquitous not only in most thermoelectric materials but also in almost all materials in our surroundings. Atomic disorder often modulates various physical properties, including their appearance (crystal color), mechanical properties, and obviously electronic and thermal transport properties, which is relevant to the discussion of this Focus Review. Electrons and phonons get scattered from the disorder and impurities present in a lattice, which consequently limits their mean free path.…”
mentioning
confidence: 99%
“…The presence of inherent atomic disorder is ubiquitous not only in most thermoelectric materials but also in almost all materials in our surroundings. Atomic disorder often modulates various physical properties, including their appearance (crystal color), 17 mechanical properties, 18 and obviously electronic and thermal transport properties, 19 which is relevant to the discussion of this Focus Review. Electrons and phonons get scattered from the disorder and impurities present in a lattice, which consequently limits their mean free path.…”
mentioning
confidence: 99%
“…[45] Nanoplasmonic structures reach scales up to centimeter-sized samples with resolutions around 100k DPI. [42,47,57,58] Dielectric materials can achieve similar resolutions but suffer from metallic counterparts' scalability issues. [31,44,46] In all these works, the mechanism of color generation relies mainly on resonant optical structures with classical shapes such as, for example, spheres, cylinders, cubes, or other longitudinally invariant forms with a constant profile under the dimension orthogonal to the sample surface.…”
Section: Introductionmentioning
confidence: 99%
“…[ 45 ] Nanoplasmonic structures reach scales up to centimeter‐sized samples with resolutions around 100k DPI. [ 42,47,57,58 ] Dielectric materials can achieve similar resolutions but suffer from metallic counterparts’ scalability issues. [ 31,44,46 ]…”
Section: Introductionmentioning
confidence: 99%